Transformasi Tiga Pilar Demokrasi Modern dalam Populisme Menurut Nadia Urbinati - Pius Pandor (Studia Philosophica et Theologica, 2019)
Populism is an old phenomenon but a new phenomenon that was brought up in power politics. Because it is something new, understanding the phenomenon of populism is also diverse. Some see it as a political movement that threatens constitutional democracy, but there are also those who see it as a movement to rejuvenate democracy. Urbinati, author of the book Me The People. How Populism Transforms Democracy, sees populism as a movement for power. According to her, populism changed the three pillars of modern democracy, namely the people (rakyat), the principle of majority (prinsip mayoritas), and the system of representation (sistem perwakilan) by reinterpreting the three. People are no longer understood as people who have sovereignty but people as masses who are united based on party, religion, ideology, and so on. The principle of majority is no longer understood procedurally to gain power but as control of others. Representation is not understood as an envoy but as ownership, whichis the embodiment of the people who have absolute power over the people. With these three transformations, according to the author, populism is a product of the failure of the malfunctions of party’s democracy